2015
DOI: 10.1371/journal.pcbi.1004240
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Effects of Electrical Coupling between Unmyelinated Axons of Brainstem Neurons Controlling Rhythmic Activity

Abstract: Gap junctions between fine unmyelinated axons can electrically couple groups of brain neurons to synchronise firing and contribute to rhythmic activity. To explore the distribution and significance of electrical coupling, we modelled a well analysed, small population of brainstem neurons which drive swimming in young frog tadpoles. A passive network of 30 multicompartmental neurons with unmyelinated axons was used to infer that: axon-axon gap junctions close to the soma gave the best match to experimentally mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 84 publications
0
36
0
Order By: Relevance
“…Previous modelling showed that these connections contribute to the synchronous recruitment of rhythmic firing in the whole population (Hull et al . ). Using this previous hdIN population model with mutual electrical coupling and excitatory synaptic connections (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous modelling showed that these connections contribute to the synchronous recruitment of rhythmic firing in the whole population (Hull et al . ). Using this previous hdIN population model with mutual electrical coupling and excitatory synaptic connections (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…However, the recruitment of reticulospinal hdINs on one side of the body by hexN excitation might also be influenced by their mutual electrical coupling and excitatory synaptic connections . Previous modelling showed that these connections contribute to the synchronous recruitment of rhythmic firing in the whole population (Hull et al 2015). Using this previous hdIN population model with mutual electrical coupling and excitatory synaptic connections ( Fig.…”
Section: Conclusion About Excitation Of Reticulospinal Hdinsmentioning
confidence: 94%
See 1 more Smart Citation
“…Modelling of the hindbrain dIN population has shown that, without electrical coupling, recruitment is gradual and often incomplete, whereas, with electrical coupling, recruitment follows a step function: where dINs are recruited all‐or‐none (Hull et al . ). This is exactly what is needed for a tadpole to decide to swim.…”
Section: Discussionmentioning
confidence: 97%
“…Modelling of the dIN population response to sensory input has shown that electrical coupling between dINs is critical to this all‐or‐none pattern of recruitment when swimming starts (Hull et al . ). Our work has defined how stimulation of trigeminal head‐skin afferents can activate a trigeminal nucleus and the reticulospinal dINs to initiate swimming on the stimulated side of the body.…”
Section: Introductionmentioning
confidence: 97%